Social Supports in Solving Marital Problems for Buddhist Couples - Phòng, Trần (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 3 No 2 (2020): ปีที่ 3 ฉบับที่ 2 ประจำเดือนกรกฏาคม - ธันวาคม 2563, 2020)
This study aims to investigate social supports in solving marital difficulties for Buddhist couples. The present research has been done on 150 lay Buddhists in Hue. The results show that 97.3%. of them put a stress on the importance of marital happiness and 2.7% of the rest did not in such a way that marital happiness was nothing to talk about. Overall, the level of difficulty in the marital life of Buddhist couples was not high (average = 1.38). Of social supports in solving marital problems for lay Buddhist, help from Buddhist temples were chosen with a higher rate.